Recombinant expression and biophysical characterization of Mrt4 protein that involved in mRNA turnover and ribosome assembly from Saccharomyces cerevisiae. Issue 4 (1st April 2022) - Kashif, Mohd; Asalam, Mohd; Al Shehri, Saad S.; Kumar, Bhupendra; Singh, Neha; Akhtar, Md Sohail
ABSTRACT: The mRNA turnover and ribosome assembly are facilitated by Mrt4 protein from Saccharomyces cerevisiae . In present study, we are reporting the cloning, expression and homogeneous purification of recombinant Mrt4. Mrt4 is a 236-amino-acid-long nuclear protein that plays a very crucial role in mRNA turnover and ribosome assembly during the translation process. mrt4 gene was amplified by polymerase chain reaction and cloned in expression vector pET23a (+) under the bacteriophage T7-inducible promoter and lac operator. Furthermore, protein was purified to homogeneity using immobilized metal affinity chromatography (IMAC) and its homogeneous purification was further validated by immunoblotting with anti-His antibody. The far-UV CD spectra represent that Mrt4 has a typical α helix with characteristic negative minima at 222 and 208 nm. At physiological pH, the fluorescence spectra and CD spectra showed properly folded tertiary and secondary structures of Mrt4, respectively. Saccharomyces Mrt4 protein possesses putative bipartite NLS (nuclear localization signal) at the N-terminal part followed by two well-conserved domains, rRNA-binding domains and translation factor (TF) binding domain. PIPSA analysis evaluates electrostatic interaction properties of proteins and concluded that Mrt4 protein can be used as a fingerprint for classifying Mrt4-like mRNA turnover protein from various species. The availability of an ample amount of protein may help in its biochemical and biophysical characterization, crystallization and identification of new interacting partners of Mrt4.